Spectral Reconstruction with Genetic Optimization in Case of Different Sample Sets - Sávoli, Zs.; Horváth, A.; Kránicz, B. (Acta Technica Jaurinensis, 2016)
Finding the spectral features of color sample sets is a main issue of colorimetry. It is widespread to apply Principal Component Analysis in these researches. Several studies were written about the reconstruction of samples with known spectra using principal components, and some works dealt with approximate reconstruction from tristimulus values. Our study examines how spectral reconstruction done with genetic optimization works in case of different sample sets. We have taken only the tristimulus values of the color samples given.